Green certification to achieve sustainable development goals - S. Kamahina, Rina (2019)
The present article initiates the idea of certifying sports facilities for compliance with innovations in the field of resource saving. The search for mechanisms to stimulate sports complexes to move to rational models of resource use led to the development of the Green Ball environmental certification program. "Green Ball" is a protocol for environmental auditing of sports facilities, summarizing all the current proposals for environmental management; website for online certification and recommendations; model of effective environmental management. If a sports facility meets these criteria, it needs to be awarded the Green Ball environmental certification mark, which, by analogy with the TRP program, can be Bronze, Silver, and Gold, which is reminiscent of hotel stars and can become a recognizable brand in the sports industry. The advantage of the site is the possibility of self-auditing to obtain recommendations that will help optimize resource use, as well as call the auditor to the object. The developed project is environmentally, economically and socially effective, which contributes to the implementation of the ideas of the concept of sustainable development in the field of sports.